THU0669 The association between harris hip score and disease activity or hip mri features in ankylosing spondylitis. (15th June 2017) - Wu, Z; He, L; Yang, M; Liu, Y; He, D; Zhang, Y; Wang, C; Xu, H
Abstract : Background: Hip involvement is a common clinical feature observed in ankylosing spondylitis (AS) patients and it often leads to substantial restriction of the body functions. 1 Hip involvement in AS is mainly assessed by radiographic changes, clinical symptoms or MRI. The Harris hip score (HHS) is a valuable assessment tool to measure health status of AS patients. However, the relationship between HHS and other clinical indices is unknown. Objectives: To evaluate relationship between HHS and other commonly used clinical indices. Methods: In this multicentre, observational study, AS patients with hip clinical manifestation are enrolled and randomly assigned to infliximab treatment (group I, with/without DMARDs and/or NSAIDs) or conventional therapy (group II, DMARDs and/or NSAIDs). Primary endpoint: to compare functional improvement of hip joint (HHS) between two treatment groups (infliximab and conventional therapy) at week 30. Secondary endpoint: to compare disease activity and functional improvement of AS and radiologic progression of hip joint between two treatment groups at week 30 and 52. Association between baseline HHS and disease activity measures such as Bath ankylosing spondylitis (BAS)-functional index (BASFI), BAS disease activity index (BASDAI), AS disease activity score (ASDAS), CRP and ESR was analysed using Pearson correlation coefficient. BAS metrology index (BASMI) and hip imaging functions (MRI of hip, BAS radiology hip index [BASRI-h]) were analysed using independent two-sample t-test or ANOVA based on data characteristics. Results: Study is ongoing; currently, only baseline information is analyzed. Baseline demographics and disease characteristics did not show any significant difference between groups. Almost all baseline disease activity measures showed significant Pearson correlation (high correlation in BASFI=0.646) with HHS, except for BASDAI (table 1 ). Significant association between HHS and three MRI scores (articular cartilage stripping, bone destruction under joint surface, femoral head bone marrow cavity edema) and BASRI-h was shown (table 2 ). Also, significant correlation was shown between BASMI and HHS (F value [degree of freedom]=4.70 [4]; p=0.0022). Conclusions: The baseline results of HHS were found to be well associated with disease activity scores like BASFI, ASDAS and BASMI and four hip imaging features in AS patients with hip involvement. References: Jeong H, et al. Korean J Intern Med. 2017; 32(1): 158–164. Disclosure of Interest: Z. Wu: None declared, L. He: None declared, M. Yang: None declared, Y. Liu: None declared, D. He: None declared, Y. Zhang: None declared, C. Wang Employee of: Xi'an Janssen pharmaceuticals Ltd., H. Xu: None declared